Dynamics of Alcohol Consumption Model with Public Awareness and Saturated Incidence - Beay, Lazarus Kalvein; Saija, Maryone; Rijoly, Monalisa E.; Lesnussa, Yopi Andry; Talakua, Mozart Winston; Ilwaru, Venn Yan Ishak (Gammarise Publishing, 2025)
This article develops a mathematical model for studying the impact of public awareness and intervention strategies on alcohol consumption patterns. To protect populations from addiction, we are focusing on educational campaigns and interventions. Alcohol consumption cases decrease as the model variable awareness susceptible class is increased through awareness campaigns and interventions. The nonnegativity and boundedness of the model's solutions are analyzed. A qualitative analysis of the model's equilibrium points and the alcohol reproductive number, R0, was performed. Global stability was analyzed for alcohol consumption at the positive equilibrium point via a suitable Lyapunov function. When the alcohol reproductive number (R0) is less than one, the alcohol-free equilibrium is globally asymptotically stable; otherwise, it is unstable. Although educational campaigns protect vulnerable people, their impact on the model is substantial. The simulation shows that the intervention directly and drastically reduces the target alcoholic population.